Prioritization of Scientific Sources of Water Information: The Effect Knowledge, Beliefs, and Political Identity - Sadie Hundemer (Journal of Applied Communications, 2023)
Scientists are reported to be more trusted than other information sources; yet, on essential water facts, people sometimes reject what they perceive water scientists to believe in favor of other belief determinants. This study examines the factors that affect the difference in people's stated willingness to reconsider their water beliefs in response to information provided by scientists relative to information provided by other sources. Regression analysis of responses provided by 806 Florida and Georgia residents found water science knowledge to be a consistently strong influencer of the gap in reliance on scientific information providers relative to other sources. This result is notable given criticisms of the knowledge deficit model. Pre-existing water beliefs had varying levels of influence, and political identity, which might have functioned as a decision heuristic, had little statistically significant effect. The study additionally found water science knowledge and water beliefs to not be strongly related. Higher scores on a water science knowledge assessment were not necessarily an indicator of accurate and knowledge-congruent water beliefs. Moreover, scientific water knowledge and water beliefs had different effects on participants’ reliance on scientific information sources.
Keywords: messenger; communicator; source; acceptance; rejection